USING SIX SIGMA TO EVALUATE ANALYTICAL PERFORMANCE OF HEMATOLOGY ANALYZER - Robiul Fuadi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Background: Many medical decisions in hospital are based on hematology examination results. We must be aware about their method performance. Sigma-metric is an excellent way to evaluate analytical performance quality. We will display the performance of our laboratory hematology analyzer, Cell Dyne Ruby, by sigma-metric analysis.Method: sigma analysis was calculated by a formula, sigma = (TEa – CV)/ Bias. Total Error Allowable (TEa) was specified by the CLIA proficiency testing criteria. The coefficien of variant (CV) and bias data were supplied from analyzer running three levels of control low (L), normal (N), and high (H) include following analytes: hemoglobin (Hb), Red Blood Cell count (RBC), Hematocrit (HCT), White Blood Cell count (WBC), and Platelet count (PLT).Results : Sigma value as follows Hb(L:4,33 N:6,68 H:2,62), RBC(L:3,43 N:3,84 H:3,46), HCT(L:2,52 N:1,73 H:2,27), WBC (L:7,14 N:8,44 H:6,38),and PLT (L:2,46 N:8,75 H:7,84). Average sigma value for all parameters were 4,75. Minimum sigma value for any business or manufacturing process was 3. More than 6 sigma value was world class performance.Conclusion: Hematology Analyzer Cell Dyne Ruby provides “Good” performance by sigma-metric.